Biological membrane lipids in norm and pathology (literature review) - S. V. Mukhomedzyanova; Yu. I. Pivovarov; O. V. Bogdanova; L. A. Dmitrieva; A. A. Shulunov (Acta Biomedica Scientifica, 2017)
This article discusses modern ideas about the structure of biological membranes, presents their basic physicochemical properties, and describes composition and structure of phospholipids from the chemical point of view. Plasmatic membrane has unique receptor-signaling functions regulating essential cellular processes, damage to which can lead to cell death. The article introduces such features of membrane lipids and proteins as fluidity or ability to lateral shift, their permeability and phase conditions; describes the effects of cholesterol on phase transitions, fluidity, elasticity, permeability and mechanical strength of the bilayer. The paper discusses transmembrane or lateral asymmetry of lipid membranes, how it is supported, and what functions it has. Different configurations of hydrocarbon chains of fatty acids and their value are considered. Because the development of various pathological processes and conditions accompanied by molecular biological changes of cell membranes, it primarily concerns erythrocyte membrane, as they are composed of many easily-oxidized phospholipids and they come in contact with relatively high concentrations of oxygen, it is important to examine the role of erythrocyte lipid layer. The impact of various damaging factors on the tissues of cells and organs triggers the universal response as consequence of such molecular mechanisms as intensification of lipid peroxidation, activation of endogenous phospholipases and proteases, reduced activity of antioxidant defense system of the cell.